Effects of high intensity interval training in normobaric hypoxia on aerobic performance and exercise-induced motor performance fatigue in young biathletes - Zebrowska, A.; Sikora, M.; Mikolajczyk, R.; Gerasimuk, D.; Thuany, M.; Weiss, K.; Knechtle, B.; Hall, B. (Journal of Sports Science & Medicine, 2025)
This study investigated the effect of high-intensity interval training (HIIT) in normobaric hypoxia on aerobic performance in young biathlon athletes. In addition, the study aimed to assess the impact of training in hypoxia on the mechanisms of exercise-induced motor performance fatigue. In a randomized, controlled crossover study twelve athletes (age 15.7 ± 1.0 years) completed a HIIT in normobaric hypoxia (hypoxia training) (fraction of inspired oxygen, FiO2 = 15.2%) and normoxia (normoxia training) in a randomized order. The HIIT was performed 3 days/week for 6 weeks (3 weeks in hypoxia and 3 weeks in normoxia, with a 3 week wash-out period in between) and consisted of 5 x 4 minutes running (80% of peak oxygen uptake), separated by 3 minutes of active recovery and 4 x 1minute arm cranking (60% peak power), interspersed with a 2 minute rest. Peak oxygen uptake (VO2peak), hypoxia-inducible factor 1 alpha (HIF1a), vascular endothelial growth factor (VEGF), pro-inflammatory cytokines, muscle damage biomarkers and total antioxidant status were analyzed before and after both training protocols (HT and NT). A significant effect of hypoxia on VO2peak (np2 = 0.321, p = 0.044) and hypoxia and training on VO2LT and haemoglobin concentrations (np2 = 0.689 p = 0.001) were observed. The VO2peak was significantly higher post-HT compared to pre-HT (p < 0.01). A significant effect of oxygen conditions and training on the serum post-exercise VEGF (np2 = 0.352, p = 0.033) and myoglobin concentrations (np2 = 0.647 p = 0.001) was found. A significant effect of hypoxia was also observed for cytokines levels: interleukin-6 (np2 = 0.324 p = 0.042), tumour necrosis factor alpha (np2 = 0.474 p = 0.009) and transforming growth factor beta (np2= 0.410, p = 0.018) with a non-significant effect on antioxidant status. This study shows significant differences in the aerobic performance and biomarkers of muscle damage after exposure to hypoxia training. These findings highlight that HIIT in hypoxia is sufficient to enhance aerobic performance and may also reduce skeletal muscle susceptibility to fatigue in young biathletes.